NOTARY AS A REPORTING PARTY IN THE ERADICATION OF THE CRIME OF MONEY LAUNDERING - Sulistyo, Edhei (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2021)
The purpose of this study is to find out and analyze the disharmony of notary arrangements as reporting parties in efforts to eradicate money laundering. This research uses qualitative methods and normative juridical approaches, as well as descriptive analytical research specifications. The results of the study indicate that the notary arrangement as one of the reporting parties in the effort to eradicate the money laundering crime regulated through a government regulation has violated the principle that the applicable laws and regulations can only changed by laws and regulations that are equivalent or higher, has also violated several principles of the formation of good laws and regulations, including institutional principles and also the principle of conformity.